Comparison of Soft Tissue Cephalometric Norms between Turkish and European-American Adults - Ahmet Arif Celebi; Enes Tan; Ibrahim Erhan Gelgor; Tugba Colak; Erdem Ayyildiz (The Scientific World Journal)
One of the most important components of orthodontic diagnosis and treatment planning is the evaluation of the patient’s soft tissue profile. The main purpose of this study was to develop soft-tissue cephalometric standards for Turkish men and women and compare them with the cephalometric standards of normal European-American white people. The sample included 96 Turkish adults (48 women, 48 men), aged 20 to 27 years. Turkish subjects have increased facial convexity associated with retruded mandible, more obtuse lower face-throat angle, increased nasolabial angle and upper lip protrusion, deeper mentolabial sulcus, and smaller interlabial gap compared with European-American white people. It is appropriate to consider these differences during routine diagnosis and treatment planning of a Turkish patient or an American patient of European ancestry. Turkish males reveal more obtuse mandibular prognathism and upper lip protrusion, and smaller nasolabial angle than females.